Pengaruh Karakteristik Petani pada Persepsi Petani dalam Pengembangan Agrowisata “Bon Deso”, Kota Batu - Pravasta Wahyu Satriawan; Sugiyanto Sugiyanto; Asihing Kustanti; Budi Sawitri (Jurnal Ilmu Pertanian Indonesia, 2024)
Developing strategic land use issues into agrotourism is increasingly prevalent in Batu City. This condition raises various kinds of farmers' perceptions about who feels the benefits of the presence of tourism. Various backgrounds make these differences in perception even more visible. This study aims to analyze the influence of farmers' characteristics on their perceptions of developing "Bon Deso" agrotourism in Tulungrejo Village, Batu City. The location of the study was determined deliberately with consideration for agrotourism activities. "Bon Deso" is located in the village. This study used quantitative survey methods with data collection techniques through interviews, observations, and instruments. The data were analyzed using descriptive statistics and simple linear regression. The population was 646, with a sample of 87 farmers obtained by calculating the Slovin formula. A simple random technique determined the sample. The results of this study show that characteristic variables simultaneously affect perception. The characteristic sub-variables that affect perception are age, length of formal education, farming experience, and land area. Characteristic sub-variables that do not influence perception are non-formal education and primary income. This finding could be used as a reference for agrotourism managers in determining programs that suit farmers. It is hoped that the presence of a program will get support and participation from farmers to maximize the development of "Bon Deso" Agrotourism. Keywords: agrotourism, farmer characteristic, farmer, perception